2016
DOI: 10.1364/oe.24.010157
|View full text |Cite
|
Sign up to set email alerts
|

Self-referenced ultra-broadband transient terahertz spectroscopy using air-photonics

Abstract: Terahertz (THz) air-photonics employs nonlinear interactions of ultrashort laser pulses in air to generate and detect THz pulses. As air is virtually non-dispersive, the optical-THz phase matching condition is automatically met, thus permitting the generation and detection of ultra-broadband THz pulses covering the entire THz spectral range without any gaps. Air-photonics naturally offers unique opportunities for ultra-broadband transient THz spectroscopy, yet many critical challenges inherent to this techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The change of the THz reflectivity, i.e., photoconductivity, was recorded as a function of time after photoexcitation at fluence 37 μJ cm −2 . The charge-carrier sum mobility μ was extracted from the peak of the photoconductivity decay curve according to the following equation 44 :…”
Section: Resultsmentioning
confidence: 99%
“…The change of the THz reflectivity, i.e., photoconductivity, was recorded as a function of time after photoexcitation at fluence 37 μJ cm −2 . The charge-carrier sum mobility μ was extracted from the peak of the photoconductivity decay curve according to the following equation 44 :…”
Section: Resultsmentioning
confidence: 99%
“…Equation (3) can be solved analytically in the case of weak photoexcitation (ΔE ≪ E 0 ) both in transmission [71] and reflection [72] geometries or numerically in the general case. The spatial dependence Δσ(z) is defined by the Lambert-Beer absorption law of the pump pulse and by averaging the local properties.…”
Section: General Considerationsmentioning
confidence: 99%
“…All of these approximations are based on a number of assumptions and approximations in terms of the probe wavelength and the magnitude of the relative change in transmission/reflection due to photoexcitation. It is important to note that improper use of these simplified equations can give a significant deviation from the expected material parameters, which may in turn lead to incorrect conclusions regarding the underlying charge-carrier dynamics of the material [6,12,59,60]. However, assessing the appropriate approximation for a given sample is not always trivial, since there are no clear boundaries for validity.…”
mentioning
confidence: 99%
“…However, assessing the appropriate approximation for a given sample is not always trivial, since there are no clear boundaries for validity. Despite this uncertainty, only a few groups have investigated the validity of these approximations in depth, and only for few specific cases in the reflection geometry [12,59]. Using a 0.33 mm undoped GaAs wafer as a case study, D'Angelo et al [59] demonstrated that the approximations of a step-like excitation and a thin film approximation are generally insufficient for extracting the transient optical properties of thin films in the reflection geometry, due to the strong phase-sensitivity of these measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation